Guillaume Apollinaire and Faik Konica: a European friendship and cooperation (Colloquia Comparativa Litterarum, 2025)
In 1903, on the road of exile, Albanian prolific and versatile author Faik Konica met a kindred spirit, Guillaume Apollinaire. The chronicle the latter published on 20 August 1903 in L'Européen Weekly and entitled War on French words in Germany would become the starting point of almost a decade of correspondence between the two men of letters. These relations would take place in a period that would become significant for their future development. In fact, their cordiality would go so far that Apollinaire would visit Konica and stay at his London home on two occasions (in November 1903 and in May 1904). Apollinaire had understood well the “double persona” Faik Konica used in his literary work: one pseudonym for his works directed towards European aestheticism, and another for the ones directed towards Balkan militancy. Konica wanted to anchor his homeland Albania in Europe, and to bring it back to where it rightfully belonged after five centuries of Orientalisation in Ottoman Asia, meeting on his way the poetry magician of Europe and of the “aesthetic of differences”. The result of the effort was that relations between Apollinaire and Konica were not random and anecdotal. They derived from deep affinities that could not be neglected. The friendship of these two “uproots” could develop and could last so long only because of the European dream they both shared.
Keywords: Guillaume Apollinaire; Faik Konica; Balkan; Europe; aestheticism